A modular path planning solution for Wire + Arc Additive Manufacturing - Michel, Florent; Lockett, Helen L.; Ding, Jialuo; Martina, Filomeno; Marinelli, Gianrocco; Williams, Stewart W. (Elsevier, 2019)
Wire + Arc Additive Manufacturing (WAAM) has proven its capability to build medium to large metallic parts thanks to its high-rate deposition and its potentially unlimited build volume. Moreover, the low-cost equipment and the ability to deposit various metals make WAAM a strong candidate to become a standard industrial process. However, like all Additive Manufacturing (AM) technologies, the key to manufacturing suitable parts lies in the generation of an optimised path that guarantees a uniform defect-free deposition. Most AM technologies have been able to use traditional path strategies derived from CNC machining, but the specificities inherent to the arc deposition make the use of those solutions unreliable across a variety of topologies. Nevertheless, studies have shown that superior results can be achieved by using a feature-based design approach, but developing a path strategy for each new geometry would be a very time-consuming task. Therefore, this paper introduces the Modular Path Planning (MPP) solution that aims to incorporate the modularity of feature-based design into the traditional layer-by-layer strategy. By dividing each layer into individual deposition sections, this method allows users to adapt the path planning to the targeted geometry allowing the construction of a wide variety of complex geometries. This paper also proposes a software implementation that limits user interventions and reduces user inputs to basic CAD modelling operations. Moreover, the MPP has been compared to a traditional path planning solution and used to build a complex part for industry.
Keywords: WAAM; Wire and Arc Additive Manufacturing; Path planning; Toolpath generation